2D and 3D Stem Cell Models of Primate Cortical Development Identify Species-Specific Differences in Progenitor Behavior Contributing to Brain Size - Otani, Tomoki; Marchetto, Maria C.; Gage, Fred H.; Simons, Benjamin D.; Livesey, Frederick J. (Cell stem cell, 2016)
Variation in cerebral cortex size and complexity is thought to contribute to differences in cognitive ability between humans and other animals. Here we compare cortical progenitor cell output in humans and three nonhuman primates using directed differentiation of pluripotent stem cells (PSCs) in adherent two-dimensional (2D) and organoid three-dimensional (3D) culture systems. Clonal lineage analysis showed that primate cortical progenitors proliferate for a protracted period of time, during which they generate early-born neurons, in contrast to rodents, where this expansion phase largely ceases before neurogenesis begins. The extent of this additional cortical progenitor expansion differs among primates, leading to differences in the number of neurons generated by each progenitor cell. We found that this mechanism for controlling cortical size is regulated cell autonomously in culture, suggesting that primate cerebral cortex size is regulated at least in part at the level of individual cortical progenitor cell clonal output. [Display omitted] •Human and primate PSCs can replicate cortical development in culture•PSC-derived cortical progenitors from different species expand to different degrees•Clonal analysis reveals marked difference in neurogenesis output over time•Species-specific timing differences in neurogenesis are regulated cell autonomously Based on modeling of cortical neurogenesis with pluripotent cells in 2D and organoid systems, Otani et al. suggest that species-specific differences in cortical size and cognitive ability between human and other animals result at least in part from cell-autonomous differences in cortical progenitor proliferation before neurogenic differentiation.